CULTURE PERFORMANCE AND ECONOMIC PROFITABILITY OF CANTANG HYBRID GROUPER (Epinephelus fuscoguttatus f x Epinephelus lanceolatus m) FINGERLINGS REARED AT DIFFERENT INITIAL STOCKING SIZES AND NURSERY PERIODS - Suko Ismi; Darmawan Setia Budi (Indonesian Aquaculture Journal, 2020)
High production costs in grouper nursery can be caused by the use of large fingerlings size and long rearing times. The purposes of this study were to evaluate the culture performance and economic profitability of “cantang” hybrid grouper juveniles reared at different initial stocking sizes and nursery periods. This research lasted from September to December 2017 in one of small scale hatcheries in Buleleng, Bali, Indonesia. This study consisted of two experimental treatments; the first treatment was different initial stocking sizes (body weight and total length) of 0.50 ± 0.07 g and 3.0 ± 2.1 cm; 3.50 ± 0.67 g and 5.0 ± 1.9 cm; and 6.10 ± 0.91 g and 7.0 ± 2.3 cm. The second treatment was different nursery periods with the following arrangement: 15, 30, and 45 days (initial body weight and length of 0.54 ± 0.067 g and 3.0 ± 0.09 cm, respectively). The stocking density in all treatments was 1,000 fish reared in a 2 m x 2 m x 1 m concrete tank. The observed culture performance parameters consisted of survival rate (SR, %), daily growth rate (DGR, g/day), and feed conversion ratio (FCR). The calculated economic profitability parameters were net profit, return-on-investment (ROI, %), and return cost ratio (R/C). The highest culture performance was achieved by the juveniles reared using the largest initial stocking size and longest nursery period. This was in contrast with the economic profitability, in which smaller initial stocking size and middle nursery period had resulted in the highest profit. Based on the culture performance and profitability considerations, the suggested combination of initial stocking size and nursery period for cantang fingerlings is 3.0 ± 2.1 cm initial stocking size and 30 days rearing times.